Merger of Bank of Rajasthan (BOR) with ICICI Bank - An Evaluation - Sharma, S. K (Journal of Commerce and Trade, 2012)
Recent takeovers include Sangli Bank in 2007, ITC Classic Finance and Anagram Finance in the years 1997 and 1998 respectively. In 2000, the bank merged with the Bank of Madura and in 2005, it acquired Russia’s Ivestitsionno Kreditny Bank. The merger of ICICI Bank and Jaipur-based BOR came into effect from 12 August after the Reserve Bank of India notified it. After the bank received permission for the merger in August 12, 2010, it said that it has successfully integrated the operations of the BOR with the ICICI Bank. The acquisition of Bank of Rajasthan by ICICI bank is the first consolidation of country’s crowded banking sector since 2008. ICICI, the country’s largest private sector lender, is offering the smaller bank’s controlling shareholders 25 shares in ICICI for 118 shares of Bank of Rajasthan. The deal, which will give ICICI a sizeable presence in the northwestern desert state of Rajasthan, values the small bank at about 2.9 times its book value, compared with an Indian banking sector average of 1.84. Post-merger, ICICI Bank’s branch network would go up to 2,463.The present paper is an attempt to throw the light on the merger of BOR with ICICI Bank. It also identifies the objectives of M&As. Some important motives and strategic issues regarding this merger have also been discussed. This paper is based mostly on secondary data. The study gives conclusion and some suggestions too.